Catamenial epilepsy - Harsono, Harsono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2002)
The true frequency of menstrually related seizures (catamenial epilepsy) is unclear. This is due in part to the fact that at present there is no universally accepted definition of this entity. Because of such arbitrary definition, a variety of therapeutic strategies for controlling seizures related to hormonal fluctuations have been recommended. With respect to the uncertainty of catamenial epilepsy criteria, the principles of physiologic changes related to hormonal fluctuations in women with epilepsy should be understood. Based on the knowledge of hormonal changes and characteristics of epilepsy, a detailed history taking should be carried out properly. This strategy will be useful for establishing diagnosis and planning appropriate treatment.Keywords: catamenial epilepsy - definition - seizure - therapeutic strategy - hormonal fluctuations.